Política de informação arquivística na Universidade Federal Rural do Semi-Árido: A Lei de Acesso à Informação - Lima, João Carlos Bernardo de (2015)
The right to information is a fundamental human right, registered in many international conventions and treaties. In this context, public information acquires a new relevance, and is considered as public interest, resulting in information policy. This study analyzes the implementation of an information policy in a federal institution of higher education. So the study of problematic questions whether the archival structure available in the institution ensures implementation and maintenance of politics. This is a descriptive research with qualitative-quantitative approach, developed through case study. Data collection occurred through the bibliographical research, individual and participant observation and interviews with the actors of the process. The sampling was non probabilistic type, defined by criteria of accessibility and typicity. The theoretical framework addresses the information, its characteristics and its social value, resulting in information policy. Analyzes the overview of the right to information, and analyzed the Brazilian Access Act to information and its impact on some social issues such as transparency in public administration. It still includes the reference the archives of public institutions and document management as essential elements in maintaining the policy of access to information. The research results have shown that even with specific disabilities, the archival structure meets the demands of users, so that the Citizens Information Service operates satisfactorily. Identified himself, however, some factors involved in the management and operation of the service. The positive factors were the performance of the service managers, archival structure and the link between the Information Service and the archival service of the institution. Ever identified negative factors were the lack of institutional support, insufficient technological capabilities, as well as the lack of knowledge on the part of service users. Given the above were presented suggestions to improve the service.